Development of Fibrous SF/PCL Tympanic Membrane Scaffolds via Electrospinning: Modeling and Experimental Verification. Issue 1 (14th December 2021) - Chen, Zhaoyu; Benecke, Lukas; Graetz, Jonas; Hümbert, Martina; Bornitz, Matthias; Aibibu, Dilbar; Cherif, Chokri; Neudert, Marcus
Abstract: The ideal tympanic membrane (TM) replacement should meet the requirement of low resistance for dynamic pressures up to about 1 Pa but high resistance for large static pressures up to about 5 kPa. Although electrospun membranes have a great potential to be used as a TM replacement, it is necessary to adjust its microstructure in order to mimic the acousto‐mechanical properties of human TM. Hence, in this work, homogenization modeling and FEM simulation of the middle ear were used to combine the microstructure of electrospun membranes to its macroscale function as TM scaffolds. The simulation results were finally verified with experimental data.